Assessment of Physicochemical, Functional, Rheological and end-use properties of Tribulus terrestris - Muhammad Usman Khalid; Muhammad Tauseef Sultan; Ahmad Mujtaba Noman; Hassan Raza; Muzzamal Hussain; Ahmed H. El-Ghorab; Mohammed M. Ghoneim; Mohamed E. Shaker; Mohamed A. Abdelgawad; Muhammad Imran; Ahmed Mujtaba; Ibrahim A. Naguib; et al. (International Journal of Food Properties, 2023)
ABSTRACTPlants are excellent food and medicinal resources because of their unique composition. Researchers have discovered that thousands of plants can help in achieving the desired health status through advanced research. This research article reveals the nutritional composition and significance of Tribulus terrestris. In addition, it also analyzed the physio-chemical evolution of nutraceutical products from Tribulus terrestris. From the proximate analysis, it was found that T. terrestris is rich in fiber and fat 24.28 ± 0.93% and 14.49 ± 1.42%, respectively. The rheological properties of the product were observed. The results reveal that water activity, stability of product, and dough development time increased 59.0 ± 0.06%, 15.0 ± 0.06 min, and 4.3 ± 0.07 min, respectively, by increasing the powder percentage. The functional behavior of the samples was examined, and significant results were depicted. Bulk density and oil absorption increased by increasing the percentage of powder 83.86 ± 1.36% and 69.16 ± 3.61%. The results of emulsifying stability were recorded as non-significant. Results regarding color analysis showed non-significant behavior of supplemented biscuits. The textural behavior of the product increased from 1.47 Nm−2 to 2.27 Nm−2. Results regarding the spread factor increased from 3.01 ± 0.04 to 3.83 ± 0.01 from T1 to T4. The sensory results indicated that T1 (2% Tribulus powder), T2 (3% Tribulus powder), T3 (4% Tribulus powder), and T4 (5% Tribulus powder) were acceptable after the control group. Thus, Tribulus terrestris can be used as a nutraceutical and functional ingredient in baked goods.